A Narrative Review of Current and Investigational Therapies in Hypertrophic Cardiomyopathy - Ian Ogurek; Randeep Gill; Vasiliki Tasouli-Drakou; Ronnie Joseph; Arbab Khalid; Nazanin Houshmand; Tahir Tak (Biomedicines, 2025)
Hypertrophic cardiomyopathy is the most prevalent inherited cardiac condition, distinguished by an autosomal dominant inheritance pattern. Diagnosis can be achieved through echocardiography, cardiac magnetic resonance imaging, and genetic testing. Recently, significant advancements have occurred in pharmacological and invasive therapies that are transforming the management of hypertrophic cardiomyopathy, including the introduction of cardiac myosin inhibitors, radiofrequency ablation, and gene editing. Additional trials are being conducted on investigational therapies, with the results anticipated in the near future. This review aims to provide a concise overview of both currently approved and investigational treatments for hypertrophic cardiomyopathy.